Abnormal thermal quenching behavior and optical properties of a novel apatite-type NaCa3Bi(PO4)3F:Sm3+ orange-red-emitting phosphor for w-LED applications. Issue 20 (15th October 2021) - Wang, Jianxu; Xie, Yan; Guo, Junlan; Yao, Xuemei; Geng, Xue; Gao, Jing; Feng, Xuyao; Zhou, Zijing; Liu, Yuanyuan; Deng, Bin; Yu, Ruijin
Abstract: Novel apatite-type NaCa3 Bi(PO4 )3 F: x Sm 3+ (0.01 ≤ x ≤ 0.30) orange-red-light phosphors were synthesized through the solid-state method at high temperature. The crystal structure, energy band structure, density of state, phase purity, particle morphology, photoluminescence properties, thermostability, and luminescence decay of the phosphors were comprehensively characterized. When λ ex = 404 nm, the optimal NaCa3 Bi(PO4 )3 F:0.05 S m 3+ phosphor showed the orange-red emission (597 nm). The NaCa3 Bi(PO4 )3 F:Sm 3+ phosphors exhibited abnormal thermal quenching properties as their emission intensity increased by about 2.57% from 300 to 380 K. Their intensity at 440 K was still 1.01-fold stronger than that at room temperature. The abnormal thermal quenching mechanisms were well explained via the coordinate configuration scheme. The thermal activation energy ( E a ) was calculated to be 0.79 eV. The color purity of all the phosphors reached 99.9%. Ultimately, a white light-emitting diode (w-LED) was fabricated based on the tri-color RGB method. The color rendering index and the chromaticity coordinates of the fabricated w-LED were 89 and (0.310, 0.319), respectively. Thus, these high thermostability NaCa3 Bi(PO4 )3 F:Sm 3+ orange-red phosphors can be potentially used in w-LED applications.